Distorsi atau Dakwah ? Kajian Pemanfaatan Hadis Dalam Konten Keislaman di Tiktok - Zulfirman Manik; Nur Fildzah Putri; Novi Irawani; Febriansyah; Faisal Fadil (Yayasan Dar Arrisyah Indonesia, 2025)
The use of hadith in Islamic content on social media has increased significantly alongside the rise of digital platforms as tools for religious outreach. However, this phenomenon raises a critical question: does the use of hadith on social media represent authentic da'wah, or does it risk distorting its meaning? This article aims to examine how hadith is conveyed, quoted, and packaged in Islamic content on social media Tiktok, and to assess its alignment with scholarly principles. Using a qualitative content analysis approach on a selection of popular posts, this study finds that while most content seeks to convey moral messages based on hadith, many overlook context, accuracy, and credible sources. The study concludes that social media Tiktok holds great potential as a medium for da'wah but also presents the risk of distortion if not accompanied by careful handling and sufficient Islamic literacy.